Evaluation of Covid-19 Surveillance in Solok Selatan District in 2021 - Yulia Astuti; Aria Gusti; Mery Ramadhani (Jurnal Kesehatan Masyarakat Andalas, 2022)
The case of COVID-19 that occurred at the end of 2019 in Wuhan, China and finally spread in almost all countries, so that in March 2020 the world health organization (WHO) declared a global pandemic. In March 2021, Indonesia was ranked 20th with confirmed positive cases totaling 1.505775. Solok Selatan Regency until June 30, 2021, the number of positive cases is 1,615. This study aims to determine the success of surveillance in terms of input, process and output as well as indicators of COVID-19 response with mixed methods. At each stage of the input, process and output there are still unfulfilled while the COVID-19 control indicators are still not running well where from the indicators studied only 40% are met, so the Health Office needs to pay attention to improve each stage that has not been met so that implementation of good COVID-19 Surveillance from the input, process and output stages and indicators of COVID-19 prevention